2014
DOI: 10.1155/2014/572025
|View full text |Cite
|
Sign up to set email alerts
|

ADAM Metallopeptidase Domain 33 (ADAM33): A Promising Target for Asthma

Abstract: Over the last few years, a significant progress has been made in understanding the role of a disintegrin and metalloproteinase 33 (ADAM33) in asthma. The previous observations for the association with asthma have been replicated in over 33 different population samples worldwide. We and others have performed association analysis and meta-analysis and provided further evidence that several polymorphisms in the ADAM33 are risk factors for asthma, especially in the Asian population. Further, several studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 48 publications
(52 reference statements)
1
34
0
2
Order By: Relevance
“…Particularly, a role of ADAM33 in that context deserves a comment. It has been demonstrated that this protein with a complex structure and function is involved in lung injury and repair . Moreover, its gene polymorphism may be associated with decrease in FEV 1 in healthy population, but also in asthmatics .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, a role of ADAM33 in that context deserves a comment. It has been demonstrated that this protein with a complex structure and function is involved in lung injury and repair . Moreover, its gene polymorphism may be associated with decrease in FEV 1 in healthy population, but also in asthmatics .…”
Section: Discussionmentioning
confidence: 99%
“…ADAM33 has been proved to play a possible role in airway remodeling due to its high expression in ASMCs, epithelium, and myo-/fibroblasts, and its function on promoting cell proliferation and differentiation. 22 Moreover, ADAM33 has been regarded as a risk factor for asthma, and higher ADAM33 mRNA expression was found in patients with both moderate and severe asthma when compared with patients with mild asthma and healthy The protein expression of ADAM33 served as the measurement data and was expressed as mean ± standard deviation. One-way ANOVA was used to analyze data, and the experiment was repeated at least three times; n = 8 per group.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a complex inflammatory disorder of airways of lungs resulting in airflow obstruction and bronchial hyperresponsiveness to a variety of stimuli and symptoms of wheeze, cough, and breathlessness [15]. The major obstacle in preventing and treating asthma has been our incomplete understanding of its etiology and biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%